THE ROLE OF MODERNIZING ISLAMIC RELIGIOUS EDUCATION AND CHARACTER BUILDING IN FACING THE CHALLENGES OF JUVENILE DELINQUENCY IN THE DIGITAL ERA - Syafi'i, Syafi'i; Shokheh, Mukhtamar (Universitas Islam Madura, 2025)
Religious education integrated with character education is a strategic solution in dealing with the negative impacts of modernization, especially among adolescents who are vulnerable to changes in values and behaviors. Modernization brings various challenges, such as the increasing influence of digital media and weak social control, which can lead to deviant behavior and a decline in the moral values of adolescents. The purpose of this study is to analyze the role of religious and character education in shaping adolescent moral behavior and suppressing adolescent delinquency in the midst of modernization. The research method used is a qualitative approach with literature study techniques, which collects and analyzes data from various journals, books, and related scientific articles. The results of the study show that religious education integrated with character education is effective in strengthening the morality of adolescents. This integration has succeeded in forming adolescents' resilience to negative influences, improving their moral reflection skills, and strengthening their identity in the face of social pressure. The implementation of integrated religious and character education has also been proven to minimize the risk of juvenile delinquency by instilling positive values and better self-control skills. The implication of this study is that this research emphasizes that the modernization of Islamic religious education plays an important role in shaping the character of adolescents, preventing delinquency, and facing moral challenges in the digital era.